Larvicide activity of two chemotypes of Hyptis suaveolens (Lamiaceae) poit, 1806 and alphacypermethrin on larvae of Rhipicepalus (Boophilus) microplus (Can., 1887) (Acari: ixodidae) - SALIFOU, SAHIDOU; SALIFOU, Soumanou; HOUNGNIMASSOUN, Houénagnon Marcel Aristide; Dotché, Ignace; ATTINDEHOU, Sabbas (My University, 2020)
Hyptis suaveolens (Lamiaceae) Poit, 1806 is a well-known herbal medicine with a variety of useful properties, including its acaricidal effect. This experiment was carried out to study the bioacaricidal activity of two chemotypes of H. suaveolens essential oil (EO) against larval of Rhipicephalus (Boophilus) microplus (Canistrini, 1887) (Acari; Ixodidae). For this purpose, five serial concentrations (0.15625%; 0.625%; 1.25%; 2.5%; and 5.00% w/v) of each chemotype of H. suaveolens were used for the larval immersion test (LIT). Larvae between 14 and 21 days old were fasted and placed in each envelope. Bioassays were performed at 27 ± 1 °C, RH 80%. Larval mortality was observed 24 h after treatment and showed 1.55–66.49% for the H. suaveolens Chemotype 1,8-cinéole (Eucalyptol) and 90.72- 99.24 of the H. suaveolens Chemotype β-caryophyllène. The LIT showed that the LC 50 and LC 95 were (45.0–138.2) mg.mL-1 and (0.0068 - 3.2) mg.mL-1 respectively. A positive correlation between H. suaveolens Chemotype β-caryophyllène EO concentration and tick control, was observed by the strong acaricidal effects against R. (B.) microplus. Our results showed that the β- caryophyllène is a promising candidate as an active raw material in the formulation of bio-acaricides against resistant strains of R. (B.) microplus.
Keywords: Chemotypes; Hyptis suaveolens; Larvicide; tick; Boophilus microplus